Gli1+ Osteogenic Progenitors Contribute to Condylar Development and Fracture Repair - Chen, Shuo; Lan, Lin; Lei, Jie; He, Yang; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2022)
The condyle plays a pivotal role in mandible development, which is regulated by various signaling molecules. The hedgehog (Hh) signaling pathway is known to modulate several processes during bone formation. However, the role of Gli1, as the read-out of Hh signaling activity, in condylar development and fracture healing has not been clarified. In this study, we discovered that a population of Gli1+ cells residing immediately below the cartilage functions as osteogenic progenitors by using Gli1-CreERT2;tdTomato mice. These Gli1+ cells contributed to nearly all osteoblasts in the subchondral bone during condyle postnatal development. Interestingly, Gli1-lineage cells could differentiate into osteoblasts and chondrocytes during fracture healing. Inhibiting Wnt/β-catenin signaling downregulated the proliferation and differentiation of Gli1+ cells in vitro. These findings suggest that Gli1+ progenitor cells participate in not only normal bone formation but also fracture healing; moreover, these cells may provide a potential target for promoting bone regeneration of the mandible.